Health Cadre Program CERDIK (smart, modern, and educational) in the UPTD Foster Area of the Sekarjaya Health Center, Baturaja, OKU - I Gusti Ayu Putu Desy Rohana; Lisdahayati Lisdahayati; Gunardi Pome; Zanzibar Zanzibar (LPPM UIKA Bogor, 2022)
Hypertension is a deadly killer without symptoms if it doesn't get proper treatment, it is commonly referred to as a silent killer. The prevalence of hypertension in South Sumatra is very high, with the 4th highest incidence on the island of Sumatra. The health problem in OKU Regency with the top number of the top 10 types of diseases is hypertension. The partner problem from the results of the preliminary study is that the delivery of hypertension treatment services, Non-Communicable Diseases (NCD) prevention service activities, and the provision of information/education are not yet optimal. The achievement of capacity-building activities for health extension workers was only 35% in 2019 in the Sekarjaya Village area. The results of interviews with health cadres obtained data that there was a lack of capacity building for health cadres in carrying out Integrated Development Post (POSBINDU) activities. The solution carried out by the service team is the development of health cadres with training and field assistance for the implementation of the Integrated Development Post (POSBINDU). The methods used are lectures, discussions, questions and answers, demonstrations, and demonstrations. Another activity is assisting the implementation of the Integrated Development Post (POSBINDU) in the UPTD Sekarjaya Health Center assisted area. The activity was attended by 30 cadres selected by village heads representing 6 (six) villages. The results of program implementation were an increase in cadres' knowledge of 27.5%, an increase in skills of 17.9% from the results of the pre and post-tests on cadres, and an increase in community visits to the BINDU Post by 92% at the end of the activity.